Perilaku Masyarakat Pesisir di Hutan Mangrove Desa Balangdatu Kabupaten Takalar - Oruh, Shermina; Nur, Hasruddin (Phinisi Integration Review, 2021)
This study aims to determine (i) the forms of coastal community behavior in mangrove forests. And (ii) the impact of community behavior on mangrove forests. This type of research is descriptive qualitative. This study aims to describe the behavior of coastal communities in the mangrove forests of Balangdatu Village and the impact of the behavior of coastal communities in the mangrove forests of Balangdatu Village, Takalar Regency. The data collection techniques are by conducting observations, interviews, and documentation. The data validation technique is source triangulation, which is to examine the credibility of the data by checking the data that has been obtained through several sources. From the results of the study found that (i) The form of behavior of coastal mangrove forest community consists of ecocentrism (preserving) and anthropocentrism (damaging). Sustainable behavior consists of community-based conservation and preservation of mangrove forests with the application of local wisdom, while destructive behavior of the community over-exploits, changes the function of mangrove lands into ponds and environmental pollution. (ii) Impacts of community behavior in mangrove forests include positive and negative impacts that affect the economic and ecological functions of mangrove forests.